(untitled) (Economic and Political Thought, 2013)
The article presents many different issues connected with the diverse attitude towards the programming periods, the assessment of state of the Program assumptions and its implementation. Moreover, the use of the European Union funds by Lower Silesian Voivodeship is thoroughly discussed.